Religion on Millennials: Phenomenon of Hijra and Changes in Islamic Landscape in Aceh - Wati, Shafrida; Alkaf, Muhammad; Idami, Zahratul (SCAD Independent, 2022)
This study examined the emergence of the phenomenon of hijra among millennials in Aceh, Indonesia, and how this phenomenon has changed the Islamic landscape. This study applied qualitative research methods while the data were collected through observation, in-depth interviews, and documentation. The research subjects consisted of 4 hijra community founders and 10 teenage members of 3 hijra communities in Langsa. These communities include Komunitas Generasi Rabbani (KGR), the Akhwat Ilmu Agama (AKHIA) and the Muslimah Aceh Fillah (MAF). This research integrated Michael Foucault's theory of power and knowledge and Jurgen Habermas’s theory of public space. The findings of this study indicated that the phenomenon of hijra among them has implications for changes in the Islamic landscape. It was triggered by the rapid development of information technology, such as the use of the internet through social media and content production on various digital platforms such as Instagram, Facebook, Twitter, and YouTube. The impact of this phenomenon fosters the autonomy of the millennials to find their interpretations and choose new religious patrons that can be accessed easily through various existing digital platforms. The emergence of these new religious patrons does not come from traditional religious institutions like dayah. Such Islamic expression will expose young Muslims to pop culture and information technology in the future.